NEW DEVELOPMENTS OF GAG «BELNIILIT» IN THE FIELD OF CENTRIFUGAL CASTING - D. A. Volkov; A. P. Merlnikov; A. D. Volkov; A. V. Mitskevich (Литьë и металлургия, 2009)
New developments of ОАО «BELNIILIT» in the field of centrifugal casting are given.